Pre-Procurement Electronic Waste Management Practices in Public Offices: The case of Hawassa City, Ethiopia - Kassahun Mitiku Yizengaw; Dr. Joe Christy (International Journal of Environmental Noise and Pollution Control, 2025)
Aim: This study aims to assess the electronic waste (e-waste) management practices in governmental offices in Hawassa City, Ethiopia, with a particular focus on the pre-procurement stages. The study seeks to identify how these offices handle e-waste and the challenges they encounter in managing it effectively. Study Design: A cross-sectional study design was used to gather and evaluate data on e-waste management practices in public offices.Place and Duration of Study: The study was conducted in governmental offices located in Hawassa City, Ethiopia. The data collection period spanned from June to July 2024. Methodology: Data were gathered from 75 organizations using a structured questionnaire. Descriptive statistics were applied to analyze the gathered data, with statistical analysis conducted using SPSS version 26. Results: The study revealed that governmental offices in Hawassa City generate substantial amounts of e-waste, particularly from computer-related devices, printers, power supplies, telecommunications equipment, displays, and cooling machines. However, few organizations have dedicated storage spaces for e-waste and those that do often mix e-waste with general solid waste, lacking proper segregation. The absence of specialized employee training and limited budgetary provisions were identified as significant barriers to effective e-waste management. Conclusion: The study highlights the critical challenges facing e-waste management in public offices, including the lack of specific e-waste legislation, awareness, national guidelines, treatment mechanisms, and proper disposal sites. It recommends segregating e-waste at the point of generation and establishing training programs for e-waste collectors, handlers, and organizational staff. The formation of an e-waste management committee and the development of operational standards are also essential to improve segregation practices and raise awareness.
Keywords: Challenges; Environment; Pre-procurement; Public offices; Waste management